2012
DOI: 10.1155/2012/263818
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Correlated Behavior of Two Light Torsion Balances and a Paraconical Pendulum in Separate Locations during the Solar Eclipse of January 26th, 2009

Abstract: On January 26th, 2009, simultaneous observations of the reactions of two very light torsion balances (Kiev, Ukraine) and a paraconical pendulum (Suceava, Romania, 440 km away) were performed during a solar eclipse that was not visible at those locations but only in the Indian Ocean. Significant correlation between the behavior of the torsion balances and the pendulum was observed. The conclusion is that a solar eclipse influences the reactions of torsion balances and pendulums, even in areas of the Earth where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Observations for the behavior of a torsind pointer during solar/lunar eclipses, and other astronomical phenomena have led to unexpected results [3][4][5][6]. The most interesting and well-documented cases are below.…”
Section: Torsind In Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations for the behavior of a torsind pointer during solar/lunar eclipses, and other astronomical phenomena have led to unexpected results [3][4][5][6]. The most interesting and well-documented cases are below.…”
Section: Torsind In Actionmentioning
confidence: 99%
“…To account for the influence of BDV we began our observations 3 days prior to this astronomical event and ended 2 days after its completion [5]. Average curves showing the background variations are shown in Figure 9 by grey lines.…”
Section: Solar Eclipse On 26012009mentioning
confidence: 99%
“…Moreover, it does not seem to matter in what part of the planet and at what time this astronomical phenomenon occurs. In addition, a number of scientific publications (see for example [4]), as well as our earlier works [5,6]) have claimed that a solar eclipse has some impact on the behavior of physical pendulums of different designs.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…These simultaneous observations have showed that devices which differ in their operating principles can react to the solar eclipse in similar ways [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the torsind responds well to syzygies [7], solar and lunar eclipses [6] [8] [14], Venus' transit [5] and other astronomical phenomena has been defined reliably. However besides the torsind very often registers strong bursts, responding to some unknown astro-space phenomena.…”
Section: Spikesmentioning
confidence: 99%